Comparative Study of Management of Intrauterine Fetal Death by Misoprostol versus Oxytocin (Ibrahim Cardiac Medical Journal, 2020)
Background & objective: Management of pregnancy with intrauterine fetal death (IUFD) is always puzzling to the obstetricians and mental agony to the patients. Intravenous oxytocin infusion was previously practiced for termination of pregnancy with IUFD. But recently misoprostol is claimed to be better than oxytocin in terms of its efficacy and safety. This prospective study was carried out to find which of these two drugs is suitable for termination of pregnancy with IUFD.Methods: Based on predefined criteria,a total of 100 singleton pregnant women with gestational age more than 22 weeks, ultrasonographically confirmed as having dead fetus in utero were included in the study and were randomly assigned to vaginal Misoprostol and Oxytocin infusion groups. The outcome was evaluated in terms of time required for induction of labor, induction to delivery time and complications encountered by each group.Result: The overall time required for induction to delivery was significantly shorter in Misoprostol group than that in Oxytocin group irrespective of their Bishop’s score (p < 0.001). Even in patients in whom the cervix was unripe (Bishop's score < 6), the mean time required from induction to delivery was much shorter in Misoprostol group (p < 0.001), but in patients in whom the cervix was ripen, the mean time from induction to delivery in Misoprostol group was shorter, but the difference did not turn to significant (p = 0.079). Both nulliparous and multiparous women experienced significantly shorter durations of labor in the Misoprostol group than those in the Oxytocin group (p < 0.001 and p = 0.001 respectively). Complications like hyperstimulation, retained placenta and postpartum hemorrhage all were somewhat higher in Misoprostol group than those in Oxytocin group, but the differences were not statistically significant (p = 0.357, p = 0.500 and p = 0.500 respectively).Conclusion: The use of vaginal misoprostol is more effective than intravenous infusion of oxytocin in induction of labor in patients with IUFD. The time required from induction to delivery is appreciably shorter when Misoprostol is used compared to that needed when oxytocin is used.Ibrahim Card Med J 2019; 9 (1&2): 74-79